Does environmental labeling exacerbate heavily polluting firms' financial constraints? Evidence from China - Han Xiao; Kemin Wang (China Journal of Accounting Research, 2020)
The Chinese Ministry of Environmental Protection has enacted an environmental policy that restricts the investment activities of heavily polluting firms by increasing their financial constraints. In this paper, we examine the impact of environmental labeling on firms' financial constraints. We document that the financial constraints of heavily polluting firms increase more than those of other firms after the issuance of environmental labeling. The debt and equity financing channels of heavily polluting firms are restricted, with smaller bank loans and less equity issuance in the future. The effect is stronger in firms that make a smaller contribution to the local government's gross domestic product, receive greater media coverage, and are located in heavily polluted provinces. The environmental regulation is effective in increasing the environmentally friendly practices and decreasing the performance growth of heavily polluting firms. Our findings not only contribute to the growing literature on the factors influencing financial constraints, identifying the effects of non-monetary factors on financial constraints, but also provide more evidence for the underlying mechanism of efficient environmental policy. Our results also provide practical suggestions for investors and institutions on evaluating firms and for regulatory authorities on further implementing environmental policy.
Keywords: 650; Environmental policy; Financial constraint